PENGARUH ETOS KERJA, DISIPLIN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA DINAS PERUMAHAN DAN PENATAAN RUANG DAERAH KABUPATEN MOROWALI - Yuliarti, Yuliarti (Katalogis, 2016)
The objectives of this research are: 1) to analyze the influence of work ethics, work discipline, and organizational commitment on civil servants performance in The Office of Housing and Spatial Planning of Morowali Regency; 2) to analyze the influence of work ethics on civil servants performance; 3) to analyze the influence of work discipline on civil servants performance; 4) to analyze the influence of organizational commitment on civil servants performance; 5) to analyze the influence of work ethics, work discipline, and organizational commitment between the civil servants and temporary employees in the office of housing and spatial planning Morowali. The type of this research is explanatory to show the influence between variables by involving 50 respondents who are selected through census method. Based on multiple linear regressions test, it is concluded that: 1) work ethics, work discipline, and organizational commitment positively and significantly influence civil servants performance in The Office of Housing and Spatial Planning of Morowali Regency; 2) work ethics positively and significantly influence civil servants performance; 3) work discipline positively and significantly influence civil servants performance; 4) organizational commitment positively and significantly influence civil servants performance; 5) work ethics, work discipline, and organizational commitment between civil servants and temporary employees show no difference